Passport, please! Travels, travails and trade - Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2018)
A country's visa policies are widely assumed to have economic consequences. In this short paper, I examine the effect of the ease with which a country's citizens can enter foreign countries on international trade. Using a specification of the gravity model that avoids the endogeneity problems that typically arise when analyzing the association between ease of travel and the extent of bilateral interactions, I find that countries which issue powerful passports experience more international trade.
urn:nbn:de:tuda-tuprints-81102
Keywords: F14; F29; F59; 330; visa; document; mobility; border; barrier